FRASA BAHASA ACEH - Mohammad Rizqi (Badan Pengembangan dan Pembinaan Bahasa, 2017)
The study aims to describe the structure and the constituents of phrases, to describe the types of phrases, to explain the sense relation of the phrase constituents, and to illustrate the possibility of the Acehnese phrases to be placed in each syntactic function. This research is a qualitative descriptive research that focuses on phrase study on Acehnese. The written data is taken from primary school books, the spoken data is taken from local news of RRI Banda Aceh and folklore. The results show that there are uniqueness of the constituents which form the coordinative phrase constructions in which they are always related by conjunctions. Numeral phrases which are formed by numeral and noun always use classifier. The structure of noun phrases which is formed of noun and noun is permanent. It means that the position of the modifier is always behind main constituents. The structure of verbal phrases, adjectival phrases, numeral phrases, and pronominal phrases are not permanent. It means that the constituent that become a modifier can be placed before or after the main constituent. The prepositional phrase has a permanent structure. ABSTRAKPenelitian ini bertujuan untuk memerikan struktur dan unsur pembentuk frasa, mendeskripsikan jenis frasa, menjelaskan hubungan makna antarunsur pembentuk frasa, dan menggambarkan kemungkinan frasa dalam bahasa Aceh untuk dapat menduduki setiap fungsi sintaksis. Penelitian ini termasuk dalam penelitian linguistik deskriptif kualitatif dengan memusatkan perhatiannya pada telaah frasa dalam bahasa Aceh. Sumber data tulis dalam penelitian ini berupa buku pelajaran tingkat sekolah dasar, sedangkan data lisan diambil dari berita daerah RRI stasiun Banda Aceh dan data dari cerita rakyat. Hasil analisis menunjukkan bahwa ada keunikan dari unsur-unsur yang membentuk konstruksi frasa koordinatif, yaitu selalu dihubungkan oleh konjungsi. Frasa numeralia yang terbentuk atas konstituen numeralia dan nomina selalu menggunakan penggolong. Struktur frasa nomina yang terbentuk dari konstituen nomina dan nomina bersifat permanen. Artinya, posisi modifikator selalu di belakang konstituen inti. Frasa verba, frasa adjektiva, numeralia, dan frasa pronomina mempunyai struktur yang tidak permanen. Artinya, konstituen yang menjadi modifikator dapat berada di depan atau di belakang konstituen inti. Frasa preposisional mempunyai struktur yang permanen.